Assessing middle ear function in infants - Kei, Joseph, 1953-; Zhao, Fei, 1965- (Plural Pub., Inc., 2012)
Although there are abundant books which describe the anatomy and physiology of hearing for adults, they do not provide adequate information about the anatomy and physiology of the auditory system of young infants under the age of seven months. This book provides an up-to-date reference source for university students, clinicians, researchers and policymakers concerned with the field of middle ear assessment. By drawing on the knowledge and expertise of experts from various countries, not only at the research level but also at the clinical level, this text represents as the only book that details the entire collection of audiological tests of middle ear function for young infants. Brought to you by two leading academics in the field of paediatric diagnostic audiology, it is written for audiology students to learn about the topic in great depth. It is also written to provide sufficient detail so as to be relevant to the broadly educated and experienced reader (such as researchers and clinicians). Coverage includes information from an international level and includes an extensive glossary of terms.